(untitled) (The New Uzbekistan Journal of Medicine, 2025)
The presented article states that the working conditions of aluminum shop workers, according to the “Hygienic classification of working conditions according to the indicators of harmfulness and danger of factors of the working environment, the severity and intensity of the labor process,” can be characterized as “harmful” with the intensity of production factors, the severity and intensity of the labor process, class 3, degree 3.